STRUKTUR DAN FUNGSI SOSIAL KEPERCAYAAN RAKYAT UNGKAPAN LARANGAN MENGENAI TUBUH MANUSIA DAN OBAT-OBATAN MASYARAKAT KENAGARIAN TANJUANG ALAM KECAMATAN TANJUANG BARU KABUPATEN TANAH DATAR - Fitri, Rahmi Yana; Juita, Novia; Nst., Muhammad Ismail (Universitas Negeri Padang, 2018)
This study is purposed to describe social structure and function of prohibitive proverb toward human body and traditional medicine in the community of Kenagarian Tanjuang Alam district Tanah Datar regency. The type of this study is qualitative with descriptive method. This study was conducted by analysis of study object with following steps: 1) described structure of community’s believe on prohibitive proverb, 2) described function of community’s believe on prohibitive proverb. Based on data analysis that had been conducted, it was obtained that people believe on prohibitive proverb toward human body and traditional medicine in the community of Kenagarian Tanjuang Alam district Tanah Datar regency has 41 proverbs. These proverbs consisted of 22 double-structures and 16 triple-structures which is the conversion located in the middle of sentence and 3 proverbs have its conversion in the end of sentence. In people believe on prohibitive proverb there are 6 proverbs that functioned to increase faith, 7 proverbs are functioned to project imagination, 19 proverbs are functioned to educate, and 41 proverbs are functioned to prohibit and one proverbs is are functioned to entertain.Keywords: structure, social function, believe, prohibitive proverb